Bird Community Composition in a Shaded Coffee Agro-ecological Matrix in Puebla, Mexico: The Effects of Landscape Heterogeneity at Multiple Spatial Scales - Leyequién, Eurídice; de Boer, W.F.; Toledo, Víctor M. (Biotropica, 2010)
This study examined the importance of habitat heterogeneity on the avian community composition, and investigated the scale at which species abundances respond to habitat variables. The study was conducted within a diverse landscape matrix of a shaded coffee region in Mexico. To detect at which characteristic spatial scale different species and foraging guilds respond most strongly we analyzed the effect of plot-, patch-and landscape-level variables at different spatial extent (i. e., different kilometer radii) on species composition and foraging guilds. We used redundancy analysis to identify species-environment correlations, and to identify predictor variables that best explained the bird community structure, quantified the influence of plot-, patch-and landscape-level variables on the bird community composition. In addition, we used the 4th-corner method to detect significant relationships between the dietary guilds and plot-, patch-and landscape-level variables. We recorded 12,335 individuals of 181 bird species; 105 bird species were recorded foraging within the shaded coffee plantations. We found that plot-and landscape-level variables significantly explained the bird community composition best across all scales, and were significantly correlated with the abundance of the dietary guilds. In contrast, patch-level variables were less important. Habitat composition variables (i. e., coffee, forest and agricultural area) were among the most important predictors. Canopy structure was more important than other vegetation structure variables in explaining dietary guild structure. Hence, the maintenance of a heterogeneous landscape with a high-quality matrix within an agro-ecological region enhances bird conservation.